2010
DOI: 10.1111/j.1365-294x.2009.04483.x
|View full text |Cite
|
Sign up to set email alerts
|

Massively parallel 454‐sequencing of fungal communities in Quercus spp. ectomycorrhizas indicates seasonal dynamics in urban and rural sites

Abstract: We analysed two sites within and outside an urban development in a rural background to estimate the fungal richness, diversity and community composition in Quercus spp. ectomycorrhizas using massively parallel 454-sequencing in combination with DNAtagging. Our analyses indicated that shallow sequencing (150 sequences) of a large number of samples (192 in total) provided data that allowed identification of seasonal trends within the fungal communities: putative root-associated antagonists and saprobes that were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
138
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(153 citation statements)
references
References 67 publications
(128 reference statements)
13
138
2
Order By: Relevance
“…Besides plants, diverse microbial communities perform many transformations that control soil properties and provide diverse ecosystem services (Harris and Birch, 1989;Bell et al, 2005;Green and Bohannan, 2006), While these microbial communities govern soil biogeochemical cycles, the structure, activity and diversity of the soil biota are sensitive to a range of biotic and environmental factors (Colloff et al, 2008;Macdonald et al, 2009;Jumpponen et al, 2010). Soil microbes may directly respond to changes in soil geochemistry (Fierer and Jackson, 2006;Rousk et al, 2010), but may also differ among plant species, particularly in the rhizosphere (Grayston et al, 1998;Lothamer et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Besides plants, diverse microbial communities perform many transformations that control soil properties and provide diverse ecosystem services (Harris and Birch, 1989;Bell et al, 2005;Green and Bohannan, 2006), While these microbial communities govern soil biogeochemical cycles, the structure, activity and diversity of the soil biota are sensitive to a range of biotic and environmental factors (Colloff et al, 2008;Macdonald et al, 2009;Jumpponen et al, 2010). Soil microbes may directly respond to changes in soil geochemistry (Fierer and Jackson, 2006;Rousk et al, 2010), but may also differ among plant species, particularly in the rhizosphere (Grayston et al, 1998;Lothamer et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The EcM communities were seasonally dynamic, differed in richness and diversity in early growing season and were comprised of members that were often unique to one host. While these and earlier data (Jumpponen et al 2010a) suggest low fungal richness and compositional shifts in urban EcM communities compared to surrounding non-urban environments, the functional consequences of these shifts remain unclear. Mycorrhizal fungi have diverse functions with a potential to facilitate nutrient uptake by accessing resources not readily available for the plants (Marschner and Dell 1994), improve drought tolerance (Lehto and Zwiazek 2011), increase disease resistance (Whipps 2004), and permit interplant transfer of nutrients through common mycelial networks (Simard and Durall 2004).…”
Section: Discussionmentioning
confidence: 81%
“…This research was motivated by our earlier effort that concluded that fungal communities associated with urban trees tend to be less species rich and compositionally distinct compared to adjacent non-urban trees (Jumpponen and Jones 2009;Jumpponen et al 2010a). Accordingly, our goal was to evaluate whether or not the choice of ornamental trees in such environments would further impact the resident fungal richness, diversity, or community composition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations